Mekaar Product Marketing Strategy towards MSMEs Developed by Unprosperous Women - Wahdini, Riski; Rokan, Mustafa Khamal; Aisyah, Siti (Universitas Pendidikan Indonesia, 2023)
The aim of this research is to find out how the Mekaar product marketing strategy is carried out by PNM Mekaar Kotanopan Branch in offering products and attracting customers to develop MSMEs. The research method used is descriptive qualitative with a type of field research to describe and find out what is happening in the field. Data collection in this research was carried out using interview techniques and direct observation at the research location to obtain information and data in the field. The source of data acquisition in this research uses primary and secondary data. The research results show that the Mekaar product marketing strategy used to offer products and attract customers in developing MSMEs is to apply the 7P marketing mix elements. PNM Mekaar raised the marketing mix concept to see whether the products or services offered can be accepted by customers, so the company must know consumer needs and desires in terms of goods or services (product), price (price). promotion and place, business actors (people), physical evidence, processes that are combined well to produce the right marketing strategy method.